Convergence of Inverse Power Method for First Eigenvalue of p-Laplace Operator. (1st November 2016) - Bozorgnia, Farid
ABSTRACT: In this article, convergence of an iterative scheme to approximate the first eigenfunction and related eigenvalue for p -Laplace operator is shown. Moreover, numerical examples are presented that show the eﬃciency and accuracy of the algorithm.